Physicochemical and Functional Properties of Flavourzyme-Mediated Protein Hydrolysate from Priacanthus hamrur Skin - Baraiya, Ravi; Renuka, Vijayakumar; Rajasree, S R Radhika (Fishery Technology, 2025)
Valorization of fish processing waste is critical for enhancing seafood processing and addressing environmental concerns. This study investigated the production of flavourzyme-mediated fish protein hydrolysate (FMPH) from the skin of Priacanthus hamrur (bull’s eye) under optimized conditions. The degree of hydrolysis and yield of FMPH were reported as 19.94 ± 0.23% and 10.52 ± 0.24%, respectively. Proximate analysis of FMPH indicated a high protein content of 91.07 ± 1.32%, low lipid content of 3.25 ± 0.30%, and ash content of 3.29 ± 0.24%. The bulk density and tapped density of FMPH were determined to be 0.29 ± 0.02 g/cm3 and 0.34 ± 0.03 g/cm3, respectively. The Hausner ratio (1.16 ± 0.15) and Compressibility Index (12.82 ± 0.64) of FMPH fell within the typical ranges of 1.12–1.18 and 11–15, respectively, indicating favourable flowability and moderate compressibility. FMPH exhibited exceptional solubility across various pH levels, with the highest solubility of 83.77 ± 0.90% at pH 7.0. The FMPH demonstrated significant water-holding capacity (0.96 ± 0.06 mL/g) and oil-holding capacity (2.51 ± 0.03 mL/g), along with notable foaming and emulsifying properties. Thisstudy demonstrated the feasibility of transforming P. hamrur skin into a high-value hydrolysate with superior functional properties, thereby supporting the sustainable utilization of fish by-products. The  results highlight the potential of FMPH for application in nutraceutical, functional food, and biopharmaceutical formulations.